HUBUNGAN MOTIVASI EKSTRINSIK DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD MUHAMMADIYAH 6 PEKANBARU - Hernilam Sharly Hotmaida; Zufriady Zufriady (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research is background by the existence of students who have low motivation, this situation is characterized by a lack of enthusiasm in the learning process activities, lack of student attention to the teacher which results in not achieving an expected goal. This study aims to determine the relationship between extrinsic motivation and mathematics learning outcomes. The type of research used is quantitative research with correlational methods. The sample was 2 classes at SD Muhammadiyah 6 Pekanbaru using Saturated Sampling techniques. Extrinsic motivation data taken from questionnaires that have been filled by students, mathematics learning outcomes data taken from odd semester exam scores. Data analysis techniques go through four stages, namely data presentation, normality test, linearity test, and hypothesis testing using the Pearson Product Moment (PPM) correlation test. From the results of data analysis, the relationship between extrinsic motivation and mathematics learning outcomes of 0.662 is relatively strong. With a contribution of 43.82%, the remaining 56.18% is determined by other variables and the significance value is t count> t table or 5.790> 1.681, then Ho is rejected, meaning there is a significant relationship between extrinsic motivation and learning outcomes in mathematics.